FD-Buffer: A Buffer Manager for Databases on Flash Disks - On, Sai Tung; Li, Yinan; He, Bingsheng; Wu, Ming; Luo, Qiong; Xu, Jianliang (Microsoft Research, 2010)
We design and implement FD-Buffer, a buffer manager for database systems running on flash-based disks. Unlike magnetic disks, flash media has an inherent read-write asymmetry: writes involve expensive erase operations and as a result are usually much slower than reads. Therefore, we address this asymmetry in FD-Buffer. Specifically, we use the average I/O cost per page access as opposed to the traditional miss rate as the performance metric for a buffer. We develop a new replacement policy in which we separate clean and dirty pages into two pools. The size ratio of the two pools is automatically adapted according to the read-write asymmetry and the runtime workload. We evaluate FD-Buffer with trace driven simulations as well as experiments on real flash disks. Our evaluation results show that our algorithm achieves up to 40% less I/O cost in simulation and up to 33% improvement on the overall performance on commodity flash disks, in comparison with the state-of-the-art flash-aware replacement policy.